Hierarchical porous cobalt monoxide nanosheet@ultrathin manganese dioxide nanosheet core-shell arrays for high-performance asymmetric supercapacitor. (17th August 2016) - Wang, Xuezhao; Xiao, Yuanhua; Su, Dangcheng; Xu, Shengang; Zhou, Liming; Wu, Shide; Han, Lifeng; Fang, Shaoming; Cao, Shaokui
Abstract: Hierarchical hybrid electrodes CoO@MnO2 nanosheet@nanosheet arrays (NNAs) for high-performance supercapacitors are designed and grown on a 3D nickel foam by a simple two step solution method combined with a post annealing treatment in Ar gas. The MnO2 nanosheets can grow directly on the CoO precursor nanosheet arrays without any pretreatment, and its thickness on the CoO NAs can also be tailored by adjusting the hydrothermal time. The NNAs with the elegant synergy between CoO and MnO2 lead to a highly enhanced areal capacitance (2.40 F cm −2 at 2.0 mA cm −2, with a wide potential window of 0.8 V). We further fabricated asymmetric supercapacitor device based on the CoO@MnO2 NNAs and active carbon, which achieved a high-energy density of 1.4 mWh cm −3 at a power density of 9.6 mW cm −3, a high power density of 192.3 mW cm −3 at 0.7 mWh cm −3 and good cyclic stability. Highlights: CoO@MnO2 core-shell nanoarray was prepared by a novel solvothermal reaction without pre-carbonization treatment. Density of MnO2 nanosheets on the CoO nanosheets can be tailored. The CoO@MnO2 delivers an ultra-high areal speciﬁc capacitance of 2.40 F cm −2 . The asymmetric supercapacitor achieves a high-energy density of 1.4 mWh cm −3 . Excellent long-term stability: 90.0% capacitance retention after 10 000 cycles.